How clinically relevant are treatment comparisons of topical calcineurin inhibitor trials for atopic eczema? - Wilkes, Sally R.; Nankervis, Helen; Tavernier, Elsa; Maruani, Annabel; Williams, Hywel C. (Elsevier, 2016)
We sought to explore the architecture of trials of calcineurin inhibitors for atopic eczema to document the extent to which comparisons with active treatments such as topical corticosteroids (TCS) might have been included or avoided. We identified all eligible randomized controlled trials (RCTs) using the Global Resource for EczemA Trials database. Network plots were produced where the nodes represented a treatment type and the lines between the nodes represented the number of trials or participants that were involved in the various treatment comparisons. A total of 174 RCTs for atopic eczema treatments were identified where pimecrolimus, tacrolimus or topical corticosteroids were compared with another intervention or a vehicle/emollient. Of 39 trials involving pimecrolimus and of 41 trials involving tacrolimus, 8 (20.5%) and 13 (31.7%) respectively made comparisons with topical corticosteroids, and 25 (64.1%) and 15 (36.6%) respectively were vehicle-controlled studies. The high rate of comparisons with vehicle controls in RCTs assessing the efficacy of pimecrolimus or tacrolimus long after efficacy had been established is a matter of concern. Active comparators (mild TCS for pimecrolimus and moderate to potent TCS for tacrolimus) are best placed to inform how topical calcineurin inhibitors compare to established clinical practice.